Fabrication of high brightness light emitting diode - Foo, Fang Wei. (2010)
This project was to design and fabricate a high-brightness GaN based light emitting diode (LED) on a <111> silicon substrate using a new light emitting disk structure to enhance the light extraction. The critical breakthrough that enabled fabrication of the first high-brightness blue LED using GaN on sapphire in the early 1990s by Shuji Nakamura of Nichia Corporation, which opened up the possibilities to create virtually any colour of light especially white LED. LED offers high luminance even on low applied voltage which is the most sought-after goal of researchers and manufacturers, and it is this device that most likely to end a hundred-year reliance on inefficient incandescent lamps. GaN on sapphire has broken new boundary to the world of LED and to tap into the world of semiconductor industry and LED on Si is another major milestone to conquer, since Si offer better thermal dissipation and possible embedded system with microchip; it has been widely experimented and studied. With Si as the substrate material to hold the LED structure and thermal dissipation, it was thinned and etched using DRIE on Si to increase its light extraction capability and efficiency. Our design not only focused on light extraction, improvement on light reflection was also encapsulated into our design by meant of using a reflection cap incorporated using wafer bonding technique. Hence different fabrication steps and materials properties had to be studied and explored to provide the best suitable solution to our LED design. All this research and exploring was to paves a way to realize our goal in fabricating of a high brightness light emitting diode using GaN on Si technology.